2015
DOI: 10.3855/jidc.5925
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting successful treatment outcomes in pulmonary tuberculosis: a single-center experience in Turkey, 2005–2011

Abstract: Introduction: We aimed to describe the treatment outcomes in patients with bacteriologically confirmed pulmonary tuberculosis (PTB) and identify factors associated with successful treatment outcome. Methodology: The medical charts of patients with smear and/or culture-positive PTB who were treated between 2005 and 2011 at the Kocaeli Tuberculosis Dispensary, Turkey, were reviewed. Patients were categorized as having a successful (cured or with a completed treatment) or poor (treatment default, treatment failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
32
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 18 publications
12
32
4
2
Order By: Relevance
“…The relatively higher proportion TB in male (53.8%) in this retrospective data is in agreement with the study conducted elsewhere (10, 1618), which could be related to the underutilization of health facility by female patients that could intern be due to various socioeconomic and cultural influences as suggested by Mohammed et al (16) or could also be due to the real biological differences between male and female in susceptibility to development of active disease (19). …”
Section: Discussionsupporting
confidence: 93%
“…The relatively higher proportion TB in male (53.8%) in this retrospective data is in agreement with the study conducted elsewhere (10, 1618), which could be related to the underutilization of health facility by female patients that could intern be due to various socioeconomic and cultural influences as suggested by Mohammed et al (16) or could also be due to the real biological differences between male and female in susceptibility to development of active disease (19). …”
Section: Discussionsupporting
confidence: 93%
“…A study in Limpopo South Africa also reported a strong association between treatment regimen and outcome of TB treatment [25]. Also, some other studies showed a higher treatment outcome in those that had no drug resistant of any form [27] [43]. Patient category or type of patient at presentation was found to significantly affect the outcome of TB treatment with new cases at presentation having the highest success rate, (85.8%) while relapse cases having the least success rate, (29.8%).…”
Section: Discussionmentioning
confidence: 95%
“…Sengul et al, reported that high educational status was significantly associated with successful PTB treatment outcome [27]. Also, Kanugo et al (2015) [38] and Sadana et al (2015) [7] both reported that better treatment outcomes were seen among literate patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations